Nyman_etal_to_DRYAD_reftableHeaders - Nyman, Tommi; Valtonen, Mia; Aspi, Jouni; Ruokonen, Minna; Kunnasranta, Mervi; Palo, Jukka U. (Dryad Digital Repository, 2014)
Text-formatted reftableHeader file containing scenarios, priors, and summary statistics used in the main DIYABC analyses